HUBUNGAN SIKAP KERJA TERHADAP KELUHAN MUSCULOSKELETAL PADA PEKERJA HOME INDUSTRY DI SURABAYA - Fara Lizenda Permatasari; Noeroel Widajati (Universitas Airlangga, 2018)
Musculoskeletal disorders were occurred in any workers, one of them are informal sector worker such as home industry in Surabaya. Works were still done manually in home industry can cause Musculoskeletal disorders (MSDs). Some of the causes of musculoskeletal disorders were work attitude. The purpose of this study was to determine the correlation between work attitude against musculoskeletal disorders. This research was an observational descriptive research with cross sectional design. Work attitude were measured using RULA (Rapid Upper Limb Assessment) The samples of this study were 20 workers who work in home industry. Data were analyzed using cross tabulation and correlation value Phi and Creamers V. The results showed that there were correlations between the work attitude with musculoskeletal disorders. Work attitude had a moderate correlation with correlation value 0.394.The conclusion of this study was work attitude had correlation with musculoskeletal disorders on home industry workers in Surabaya. High-risk work attitude can occur by poor work station condition.Keywords: home industry, musculoskeletal disorders, work attitude